Molecular traces of invasion: eDNA-based high-resolution mapping of Nile tilapia (Oreochromis niloticus) across freshwater habitats of West Bengal, India - Das, Basanta Kumar; Mandal, Biswajit; Kumar, Vikash; Roy, Suvra; Dalal, Snehasis; Samanta, Srikanta (Frontiers in Marine Science, 2025)
Invasive species pose significant threats to native biodiversity, ecosystem stability, and the sustainability of fisheries. The Nile tilapia (Oreochromis niloticus), a highly adaptable invasive fish, has rapidly proliferated across the aquatic ecosystems of Eastern India, necessitating precise and efficient monitoring strategies. This study employed environmental DNA (eDNA) analysis to assess the distribution of O. niloticus across multiple aquatic habitats, leveraging species-specific primers enabled high-resolution detection. eDNA signatures were successfully amplified from sediment and direct tissue samples, with sequences submitted to NCBI (PQ810007, PQ810734, PQ814753, PQ814801, PQ821106), confirming the widespread presence of species. Spatial heterogeneity in physicochemical parameters influenced eDNA persistence and detection efficiency, with temperature, pH values, and sediment composition playing crucial roles. Sand-dominated substrates facilitated rapid DNA percolation and loss, whereas finer sediments enhanced retention. PCR validation demonstrated high specificity, with no cross-reactivity with non-target species, reinforcing the robustness of the primer design. Despite successful amplification in lentic environments, the absence of O. niloticus eDNA in Kolaghat, Akaipur, and Ganga River sediments suggests either low species abundance or rapid degradation in high-flow systems. These findings underscore the influence of hydrodynamic conditions on eDNA stability, emphasizing the need for habitat-specific sampling strategies. This study establishes eDNA as a powerful, non-invasive tool for invasive species monitoring, bridging molecular ecology with conservation management. Future research should refine molecular protocols, integrate hydrodynamic modeling, and optimize eDNA sampling methodologies to enhance surveillance accuracy. The study highlights the urgent need for targeted mitigation strategies to control O. niloticus populations and protect native biodiversity, advocating for eDNA-based monitoring as a cornerstone in global invasive species management frameworks.